Bradycardia and Asystole in Patients Undergoing Symptomatic Chronically Occluded Internal Carotid Artery Recanalization. (16th November 2020) - Hudson, Joseph S; Zanaty, Mario; Wadman, Victoria; Nakagawa, Daichi; Ishii, Daizo; Roa, Jorge A; Kasab, Sami Al; Limaye, Kaustubh; Rossen, James D; Jabbour, Pascal; Adams, Harold; Samaniego, Edgar A; et al.
Abstract: INTRODUCTION: Reports have emerged describing the successful endovascular recanalization of chronically occluded cervical internal carotid arteries (COICA). The impact this restoration of flow has on the sensitive carotid sinus baroreceptors has not been previously described. In this manuscript we present the largest COICA surgical series to date, with a specific focus on perioperative heart rate abnormalities. METHODS: Patient demographics were obtained, and the COICAs were radiographically classified based on the anatomic distribution of the stenosis and collateral flow. 36 patients had a total of 37 COICA revascularization procedures. RESULTS: 23 patients had intra-procedural bradycardia during balloon angioplasty. 3 patients went into transient asystole during the procedure. 2 of these patients had symptomatic bradycardia with ischemic cerebral changes, one of which required permanent pace-making. All other patients had immediate resolution of their bradycardia, asystole, and neurologic symptoms immediately following balloon deflation and pharmaceutical management. There was a statistically significant difference in the observed proportion of bradycardic patients amongst COICA classifications ( P = . 014). There was no statistically significant difference in mean age between patients with bradycardia and those without (63.36 years old vs 67.71 years old, P  = .2265). CONCLUSION: Bradycardia associated with angioplasty of the carotid bulb was observed in the majority of patients receiving COICA revascularization. A small percentage of these patients were symptomatic. Our results suggest that carotid sinus baroreceptors remain active whilst residing in a complete arterial occlusion, and close monitoring is necessary during balloon angioplasty of the proximal COICA.